The Effect of PEG (Polyethylene Glycol) 6000 on Water Spinach (Ipomoea reptans L.) Growth - Annisa Nurul Fathia; Tundjung T. Handayani; Zulkifli Zulkifli; Martha L. Lande (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2020)
The purpose of this research was to know whether PEG 6000 can decrease the growth of water spinach. This study was conducted in a Completely Randomized Design with main factor is PEG with 3 levels ofconcentration: 0% w/v, 10% w/v, 20% w/v and 30% w/v with 5 repetitions. As parameters were plantheight, number of leaves, fresh weight, dry weight, and relative water content. Levene test, analysis ofvariance, and Tukey test were conducted at 5% level. The result shows that the plant period is positivelylinearly correlated with plant height at all PEG concentrations with different growth rates. Lowest growthrate at 20% and 30% PEG concentrations. PEG with 20% and 30% concentrations significantly decreasein the number of leaves, wet weight, dry weight, but there is no effect on relative water content. Theconclusion is water stress conditions will decrease the growth of water spinach.